Phenolic compounds and antimicrobial activity of olive (Olea europaea L. Cv. Cobrancosa) leaves. - Pereira, Ana Paula (2008)
We report the determination of phenolic compounds in olive leaves by reversedphase HPLC/DAD, and the evaluation of their in vitro activity against several microorganisms that may be causal agents of human intestinal and respiratory tract infections, namely Gram positive (Bacillus cereus, B. subtilis and Staphylococcus aureus), Gram negative bacteria (Pseudomonas aeruginosa, Escherichia coli and Klebsiella pneumoniae) and fungi (Candida albicans and Cryptococcus neoformans). Seven phenolic compounds were identified and quantified: caffeic acid, verbascoside, oleuropein, luteolin 7-O-glucoside, rutin, apigenin 7-O-glucoside and luteolin 4’-O-glucoside. At low concentrations olive leafs extracts showed an unusual combined antibacterial and antifungal action, which suggest their great potential as nutraceuticals, particulalry as a source of phenolic compounds.